2013
DOI: 10.3892/br.2013.63
|View full text |Cite
|
Sign up to set email alerts
|

Treg/Th17 imbalance is associated with cardiovascular complications in uremic patients undergoing maintenance hemodialysis

Abstract: Abstract.Investigations of Treg/Th17 imbalance associated with cardiovascular complications in hemodialysis are limited. The aim of this study was to examine the association between Treg/Th17 balance and cardiovascular comorbidity in maintenance hemodialysis (MHD). Uremic patients included in the present study were divided into three groups: the WHD group comprising 30 patients with no cardiovascular complications or maintenance hemodialysis (MHD), the MHD1 group comprising 36 patients presenting with cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This enzyme can effectively down-regulate the T-cell receptor (TCR) ζ-chain [22], which has been documented in HD patients [23]. In recent years, Treg and Th17 cells, as a subclass of CD4 + T cells, were shown to be involved in inflammatory responses in uremic patients who underwent treatment with HD [24]. This study explored the potential functionality of a Treg/Th22 cell imbalance in microinflammation of uremic patients who underwent HD, and the results revealed that a Treg/Th22 cell imbalance participated in microinflammation that induced uremia progression in patients undergoing HD.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme can effectively down-regulate the T-cell receptor (TCR) ζ-chain [22], which has been documented in HD patients [23]. In recent years, Treg and Th17 cells, as a subclass of CD4 + T cells, were shown to be involved in inflammatory responses in uremic patients who underwent treatment with HD [24]. This study explored the potential functionality of a Treg/Th22 cell imbalance in microinflammation of uremic patients who underwent HD, and the results revealed that a Treg/Th22 cell imbalance participated in microinflammation that induced uremia progression in patients undergoing HD.…”
Section: Discussionmentioning
confidence: 99%
“…T helper (Th) dysregulation is strongly associated with long term uremia especially in patients displaying cardiovascular complications [ 13 ]. Renal replacement therapy has been shown to influence this dysregulation as compared to healthy controls [ 14 ].…”
Section: Introductionmentioning
confidence: 99%